The injury patterns, management and outcomes of retroperitoneal haemorrhage caused by lumbar arterial bleeding at a Level-1 Trauma Centre: A 10-year retrospective review. Issue 1 (January 2023) - Schlegel, R.N.; Fitzgerald, M.; O'Reilly, G.; Clements, W.; Goh, G.S.; Groombridge, C.; Johnny, C.; Noonan, M.; Ban, J.; Mathew, J.
Highlights: Patients with haemorrhage due to bleeding of the lumbar arteries have a higher rate of lumbar transverse process fractures. Patients with lumbar artery bleeding also have a greater number of massive transfusions, higher injury severity score and shock index. Lumbar transverse process fractures in a shocked patient may predict haemorrhage requiring early, aggressive intervention. Lumbar artery bleeds are best managed in Level-1 or Level-2 trauma facilities equipped with angioembolisation facilities or hybrid theatres. Abstract: Purpose: Haemorrhagic shock remains a leading preventable cause of death amongst trauma patients. Failure to identify retroperitoneal haemorrhage (RPH) can lead to irreversible haemorrhagic shock. The arteries of the middle retroperitoneal region (i.e., the 1st to 4th lumbar arteries) are complicit in haemorrhage into the retroperitoneal space. However, predictive injury patterns and subsequent management implications of haemorrhage secondary to bleeding of these arteries is lacking. Materials and methods: We performed a retrospective cohort study of patients diagnosed with retroperitoneal haemorrhage who presented to our Level-1 Trauma Centre (2009–2019). We described the associated injuries, management and outcomes relating to haemorrhage of lumbar arteries (L1–4) from this cohort to assess risk and management priorities in non-cavitary haemorrhage compared to RPH due to other causes. Results: Haemorrhage of the lumbar arteries (LA) is associated with a higher proportion of lumbar transverse process (TP) fractures. Bleeding from branches of these vessels is associated with lower systolic blood pressure, increased incidence of massive transfusion, higher shock index, and a higher Injury Severity Score (ISS). A higher proportion of patients in the LA group underwent angioembolisation when compared to other causes of RPH. Conclusion: This study highlights the injury patterns, particularly TP fractures, in the prediction, early detection and management of haemorrhage from the lumbar arteries (L1–4). Compared to other causes of RPH, bleeding of the LA responds to early, aggressive haemorrhage control through angioembolisation. These injuries are likely best treated in Level-1 or Level-2 trauma facilities that are equipped with angioembolisation facilities or hybrid theatres to facilitate early identification and management of thoracolumbar bleeds.